Neurological disorders after hysterectomy: from pathogenesis to clinical manifestations - A. G. Solopova; D. V. Blinov; E. Begovich; L. N. Sandzhieva; S. V. Demyanov; G. V. Demyanov (Эпилепсия и пароксизмальные состояния)
Hysterectomy currently occupies one of the leading places among obstetric and gynecological surgeries and is one of the highly effective and sometimes the only method of treating various diseases of the female genital organs.  Quite often, however, hysterectomy results not only in the elimination of the cause of disease, but also in the development of complications that reduce the quality of life of patients. More and more attention is being paid to neurological complications, which is obviously due to improved diagnostic capabilities, as well as the results of recent research on the pathogenesis and treatment of neurological disorders. Only recently the scientists have begun to think about the true causes  of one of the most important neurologic complications of hysterectomy, namely chronic postoperative pain.The review describes in detail the main neurological disorders that develop after hysterectomy: chronic postoperative pain, traumatic neuroma, residual ovarian syndrome  as possible causes of chronic pain, mononeuropathies, sexual and sleep disorders, decreased cognitive and motor functions, lower  urinary tract and bowel dysfunction.  Considerable  attention is given to the mechanisms of neurological complications and the relationship between the surgery and emotional disturbances in women.